2021
DOI: 10.1039/d1sc04647k
|View full text |Cite
|
Sign up to set email alerts
|

15N-Azides as practical and effective tags for developing long-lived hyperpolarized agents

Abstract: Azide moieties, unique linear species containing three nitrogen atoms, represent an attractive class of molecular tag for hyperpolarized magnetic resonance imaging (HP-MRI). Here we demonstrate (15N)3-azide-containing molecules exhibit long-lasting hyperpolarization lifetimes up...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In another study by Bae et al, triply labeled 15 N 3 -AZT and singly labeled 15 N 14 N 2 -AZT hyperpolarized by d-DNP showed T 1 values of 2.5-5.3 min (1 T). 45 In this study, the singly labeled 1- 15 N center was affected by the scalar relaxation with neighboring 14 N (I ¼ 1), leading to unmeasurable T 1 at 1 T. These studies exemplify the synthesis of 15 N-labeled drug molecules with the potential to monitor drug activities.…”
Section: N-enriched Endogenous Molecules and Drugsmentioning
confidence: 74%
See 1 more Smart Citation
“…In another study by Bae et al, triply labeled 15 N 3 -AZT and singly labeled 15 N 14 N 2 -AZT hyperpolarized by d-DNP showed T 1 values of 2.5-5.3 min (1 T). 45 In this study, the singly labeled 1- 15 N center was affected by the scalar relaxation with neighboring 14 N (I ¼ 1), leading to unmeasurable T 1 at 1 T. These studies exemplify the synthesis of 15 N-labeled drug molecules with the potential to monitor drug activities.…”
Section: N-enriched Endogenous Molecules and Drugsmentioning
confidence: 74%
“…Azides, unique linear species containing three nitrogen atoms, have been known as bioorthogonal reactive partners and possess desired features for a molecular tag. 75,76 15 N-Azides have been demonstrated as another class of 15 N-molecular tags for hyperpolarized imaging by Bae et al 45 Triply labeled 15 N 3 -azides have been incorporated into choline, glucose, and tyrosine analogs for investigation. Hyperpolarization of all these 15 N 3 -tagged molecules by d-DNP demonstrated long lifetimes up to 9.8 min (1 T) (Fig.…”
Section: Hyperpolarized 15n Probesmentioning
confidence: 99%
“…57−60 For example, DNP-hyperpolarized 15 N-pyridine displayed a remarkable ability to elucidate pH, with over a 90 ppm chemical shift dispersion over 2.1−8.5 pH range. 61 Other notable DNP-hyperpolarized 15 N agents include azides and their derivatives 62 as well as nitrate. 63 In addition to DNP studies, both hydrogenative PHIP and nonhydrogenative SABRE demonstrated hyperpolarization of 15 N-containing compounds, including choline 64 and other 15 N-hyperpolarized markers.…”
Section: N] P In This Document)mentioning
confidence: 99%
“…In addition, 15 N-enriched molecules acting as environmental sensors have also been investigated. For example, DNP-hyperpolarized 15 N-pyridine displayed a remarkable ability to elucidate pH, with over a 90 ppm chemical shift dispersion over 2.1–8.5 pH range . Other notable DNP-hyperpolarized 15 N agents include azides and their derivatives as well as nitrate . In addition to DNP studies, both hydrogenative PHIP and nonhydrogenative SABRE demonstrated hyperpolarization of 15 N-containing compounds, including choline and other 15 N-hyperpolarized markers. , For a general overview mapping the progress of 15 N hyperpolarization using SABRE, we point to review articles in refs , .…”
Section: Introductionmentioning
confidence: 99%
“…Compared to carbon-13-labeled probes, nitrogen-15-labeled agents are relatively underexplored as hyperpolarization probes. Among the hyperpolarization studies reported, the 15 N-labeled hyperpolarized probes have shown great potentials to deliver a long T 1 and a wide range of 15 N chemical shift (900 ppm) for an extended scope of chemical complexity. Notably, the T 1 of 15 N-trimethylphenylammonium was reportedly over 400 s although the oxidative reaction afforded a small chemical shift (∼1.5 ppm).…”
mentioning
confidence: 99%